Optimalisasi Pengelolaan Pariwisata Dan Peningkatan Promosi Melalui Konten Visual Di Desa Wisata Melung - Fiby Nur Afiana; Zanuar Rifai; Anugerah Bagus Wijaya; Tarsono Chris Michael Oktaviano; Salsabilla Nadya Pangestika (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2024)
As a tourist village, village development is not an easy thing. There is a lot of work and obstacles faced by the village government and the people of Melung Tourism Village. One of the obstacles faced is in terms of Human Resources (HR) management. So it is very important to develop their skills so they can revive their village and benefit from it. The next problem is that the Pagubugan tourist attraction is more famous than the Melung Tourism Village, and this is a challenge in itself for the Melung Tourism Village because many tourists are more familiar with Pagubugan than the Melung tourist village and other tourist packages are not well exposed. The Melung Tourism Village Social Media account is not managed well in terms of content, both photos and videos are less interesting so that it does not make users intrigued or curious enough to come directly to the tourist attraction. The Amikom University Lecturer Team held service activities for creative digital groups with the aim of increasing promotion through visual content in the Melung Tourism Village. The training provided can increase HR knowledge regarding techniques for taking and editing photos and videos that will be published on promotional media, this can be seen from one of the advantages of promotional media which is easier to go viral and reaches a wider community so that the Melung Tourism Village can be known to the wider community and able to compete with other tourist attractions in Banyumas Regency.